The impact of relaxation massage on ovulation and sexual appetite - Lucian Șerbănescu; Vadym Rotar; Paris Ionescu; Mihai Mitran; Sebastian Mirea; Alexandra-Ecaterina Ciota (Balneo and PRM Research Journal)
Massage therapy, a traditional practice, has garnered interest for its potential applications in re-productive health, particularly in enhancing fertility and hormonal balance. This study investi-gates the impact of ovulation-inducing massage on monthly ovulation rates among women seeking fertility assessment. Conducted at Santerra Medical Center, this three-month study involved 60 women divided into two groups: one receiving massage therapy (n=32) and a control group without massage (n=28). Ovulation was monitored using transvaginal ultrasound and urinary ovulation tests. The massage group exhibited a monthly ovulation rate of 75%, compared to 57.1% in the control group. Additionally, 18.7% of the massage group experi-enced intermittent ovulation, slightly higher than 17.8% in the control group. Notably, the per-centage of women with no ovulation was lower in the massage group. The findings suggest that massage may enhance ovulatory function through increased blood flow to the re-productive organs, reduced cortisol levels, and improved lymphatic drainage. Previous litera-ture supports the benefits of massage in various health conditions, including reproductive health. Despite literature suggesting that 80-90% of women ovulate monthly, our study found a rate of only 57.1%, potentially linked to stress factors, nutrition, and gynecological conditions. However, massage therapy showed a significant positive effect on ovulation induc-tion, underscoring its value in enhancing conception rates by reducing stress and improving lo-cal blood flow and increasing the sexual appetite. These results highlight the potential of inte-grative approaches like massage therapy in supporting reproductive health.